DEVELOPMENT OF SHORT FILM BASED ON LOCAL CULTURE FOR P5 IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Sofyan, Sofyan; Habibi, Akhmad; Hendra, Robi (Indonesian Journal of Educational Development (IJED), 2023)
This research aims to develop a short film based on local culture for the Strengthening Pancasila Student Profile Project (P5). Development was carried out using the research and development (R&D) method according to Lee and  Aka (2019). This model includes five main steps, namely: 1) needs assessment and analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. To obtain validity and response, an evaluation model developed by Vaughan, (2006) was carried out using the format of ongoing evaluation, alpha test and beta test. The results of product validity testing carried out by learning technology experts, learning media experts and material experts concluded that the short documentary film based on local culture and history for P5 was declared valid with very good and appropriate criteria with an average validity level of 89.27%. The results of trials on 36 students in class Film media facilitates students' positive attitudes such as increasing learning motivation, helping understanding cultural and historical literacy with an acceptance rate of 83.31%. In conclusion, the short film developed is valid, practical and easy to use.